ILC1s in Tissue Inflammation and Infection - Fuchs, Anja (Frontiers in Immunology, 2016)
Innate lymphoid cells (ILCs) are innate immune cells that provide an early source of cytokines to initiate and tailor the immune response to the type of the encountered pathogen or insult. The group 1 ILCs are comprised of conventional natural killer (cNK) cells and subsets of “unconventional NK cells", termed ILC1s. Although cNK cells and ILC1s share many features, such as certain phenotypic markers and the ability to produce IFN-γ upon activation, it is now becoming apparent that these two subsets develop from different progenitors and show unique tissue distribution and functional characteristics. Recent studies have aimed at elucidating the individual contributions of cNK cells and ILC1s during protective host responses, as well as during chronic inflammation. This review provides an overview of the current knowledge of the developmental origins, as well as of the phenotypic and functional characteristics of ILC1s.